2015
DOI: 10.4238/2015.february.13.12
|View full text |Cite
|
Sign up to set email alerts
|

Random amplified polymorphic DNA analysis of salt-tolerant tobacco mutants generated by gamma radiation

Abstract: ABSTRACT. Salinity is one of the major problems limiting the yield of agricultural products. Radiation mutagenesis is used to improve salttolerant mutant plants. In this study, we aimed to improve salt-tolerant mutants of two oriental tobacco varieties. One thousand seeds of each variety (M 0 ) were irradiated with 100, 200, 300, and 400 Gy gamma rays by Cs-137 gamma. In the M 1 generation, 2999 single plants were harvested. The next season, these seeds were bulked and planted to obtain M 2 progeny. The seeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Cross-breeding to breed salt-tolerant varieties has become a vital topic in the academic research of salt-tolerant plant breeding [3]. However, because of the long breeding cycle of kiwifruit, the genetic improvement process of cross-breeding is seriously hindered [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-breeding to breed salt-tolerant varieties has become a vital topic in the academic research of salt-tolerant plant breeding [3]. However, because of the long breeding cycle of kiwifruit, the genetic improvement process of cross-breeding is seriously hindered [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Gamma radiation is well known to cause rapid and reliable physicochemical and biological alterations in organisms. [14][15][16] In mutation breeding studies, the next crucial step is to select the desired genotypes for new cultivars. Due to the fact that the selected mutants from M2 and M3 generations differ for several traits, it is important to discriminate the desired genotypes to improve new cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that 10 Gy gamma irradiation was found as the most effective dose to induce genetic variation in morphological traits, and they observed 100% polymorphism among the mutants. Gamma radiation-induced salt-tolerant oriental tobacco mutants were improved by Çelik and Atak [23]. Salt tolerance of the mutants was controlled by the callus induction in the presence of high salt concentration.…”
Section: Mutational Genomic Analysismentioning
confidence: 99%
“…RAPD is an efficient method to detect DNA alteration via using random primers. It has been started to use in earlier studies of genetic variabilities obtained by radiation treatments in Chrysanthemum [36,37], soybean [24], sugarcane, sunflower, groundnut [43], tobacco [23], potato [27], Rhododendron [25]. ISSR method is another molecular marker method widely used in plant biotechnology applications.…”
Section: Mutational Genomic Analysismentioning
confidence: 99%
See 1 more Smart Citation